Employee Engagement and Organizational Performance of Public Enterprises in Nepal - Shrestha, Rupa (The International Research Journal of Management Science, 2019)
Background: 'Employee Engagement’ has been a considerable topic in the public sector. It is a buzz word that managers think they understand, but face difficulties and challenges while practicing. Objective: This study aims that employee engagement impacts on organizational performance in some extent. Drawing on theory “Employee Engagement and Higher Work Ethic", (The Gallup Organization, 2013), this study examines the relation between employee engagement and organizational outcome. Methodology: Based on descriptive analysis, this study consisted officer level employees from Tribhuvan University from 49 campuses and offices as respondents. The data was collected through 115 set of structured questionnaires during last three months of 2075 BS and It used descriptive and inferential statistics tools to analyze the data. Result: It was hypothesized that the employee engagement was positively related to the organizational performance with liking of work force diversity. It is revealed that majority employees of TU are engaged with work and organization as well. During the analysis, the hypothesis was supported with 0.505r2 (50 percentages). It was also found that explanatory and dependent variables are correlated with 0.696. Conclusion: It can be concluded that there is significant relation between organizational performance and employee engagement. Employees, who are engaged with jobs can understand social cues among the others thus they can choose the way to improve social skills in order to achieve organizational goals. This study also complies that the relation between employee engagement and performance is diverse as per work force patterns in work place. Implication: This research stimulates researchers to begin to think about how employee engagement relates to HR and organizational outcome. Public enterprises should always try to make employees engaged and transform not engaged and disengaged employees to engaged ones which ultimately leads to enhance organizational culture.